Associations of fluoride intake with children's cortical bone mineral and strength measures at age 11. (29th August 2018) - Levy, Steven M.; Eichenberger‐Gilmore, Julie M.; Warren, John J.; Kavand, Golnaz; Letuchy, Elena; Broffitt, Barbara; Marshall, Teresa A.; Burns, Trudy L.; Janz, Kathy F.; Pauley, Cynthia; Torner, James C.; Phipps, Kathy
Abstract: Objectives: There is strong affinity between fluoride and calcium, and mineralized tissues. Investigations of fluoride and bone health during childhood and adolescence show inconsistent results. This analysis assessed associations between period‐specific and cumulative fluoride intakes from birth to age 11, and age 11 cortical bone measures obtained using peripheral quantitative computed tomography (pQCT) of the radius and tibia ( n = 424). Methods: Participants were a cohort recruited from eight Iowa hospitals at birth. Fluoride intakes from water, other beverages, selected foods, dietary supplements, and dentifrice were recorded every 1.5–6 months using detailed questionnaires. Correlations between bone measures (cortical bone mineral content, density, area, and strength) and fluoride intake were determined in bivariate and multivariable analyses adjusting for Tanner stage, weight and height. Results: The majority of associations were weak. For boys, only the positive associations between daily fluoride intakes for 0–3 years and radius and tibia bone mineral content were statistically significant. For girls, the negative correlations of recent daily fluoride intake per kg of body weight from 8.5 to 11 years with radius bone mineral content, area, and strength and tibia strength were statistically significant. No associations between cumulative daily fluoride intakes from birth to 11 years and bone measures were statistically significant. Conclusions: In this cohort of 11‐year‐old children, mostly living in optimally fluoridated areas, life‐long fluoride intakes from combined sources were weakly associated with tibia and radius cortical pQCT measures.